Emergency Department Well‐being Initiatives During the COVID‐19 Pandemic: An After‐action Review. Issue 4 (1st July 2020) - Zaidi, Sara R.; Sharma, Vineet K.; Tsai, Shiu‐Lin; Flores, Stefan; Lema, Penelope C.; Castillo, Jenny
Abstract: The COVID‐19 pandemic has significantly impacted the well‐being of our health care professionals, particularly frontline providers in the emergency department (ED). Our ED, located in New York City, was severely affected, exposing the staff to a combination of unique stressors. Our ED Wellness Committee responded by implementing various initiatives focusing on the physical, mental, and social needs of our providers to support them through this difficult time. The initiatives we describe offer a framework that may help other departments understand the importance of provider well‐being during a pandemic.